Research on the characteristics of ancient kazakh vocabulary (Eurasian Journal of Philology Science and Education, 2019)
This article takes examples of the fixed and loan words in the kazakh documents from the 18th to 19th centuries, and based on the research theories of historical comparative linguistics and historical philology, preliminary analyzes the characteristics of ancient kazakh vocabulary. For example, the fixed words of ancient kazakh vocabulary are divided into nine, and the loan words are divided into six subsections for detailed study. At the same time, it also emphasizes they leading role in the systematic study of kazakh language development history and the importance of kazakh lexical science research.